Citizenship, faith, & feminism : Jewish and Muslim women reclaim their rights - Feldman, Jan L. (Jan Lynn), 1955- (Brandeis series on gender, culture, religion & law., 2011)
The first book to examine religious feminist activists in Israel, the U.S., and Kuwait.